Analisis Perbandingan Penilaian Kerusakan Jalan Metode Bina Marga Dan Metode Pavement Condition Index (PCI) (Studi Kasus : Jalan Ratu Sima Kota Dumai) - Febri Rahman; M Yusa; Elianora Elianora (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Road is a land transportation infrastructure that is very important because if the road a good area, facilitate the economic activities of the community, facilitate the mobility of the population, increase productivity in work and increase other social activities. Damage to the road will disturb the comfort in driving, such as Ratu Sima street which has many flexible pavement. Ratu Sima Street is one of the roads in Dumai City. The purpose of this study is to assess and classify the types and extent of pavement damage, and to determine the value of pavement conditions by finding the value of Pavement Condition Index (PCI) and Bina Marga. The assessment of pavement condition is needed to establish the appropriate maintenance program. The methods that usually used to evaluate pavement condition are the method of Bina Marga and PCI (Pavement Condition Index) method. This study aims to assess the pavement condition of Ratu Sima street with these two methods being compared. This study used field research in which the primary data was the result of pavement condition survey. The priority of pavement maintenance of Bina Marga method rated from 0 to more than 7, while the PCI rated from 0 to 100. Result of evaluation of condition of Ratu Sima street with Bina Marga method and the PCI method turns out to result in different assessments, the Bina Marga method obtains periodic maintenance results and the PCI method gets failed results. Key words: pavement condition index, Bina Marga, PCI.